Real-Time Visualization of the Infection and Replication of a Mouse-Lethal Recombinant H9N2 Avian Influenza Virus - Lao, Guangjie; Ma, Kaixiong; Qiu, Ziwen; Qi, Wenbao; Liao, Ming; Li, Huanan (Frontiers in Veterinary Science, 2022)
H9N2 avian influenza viruses (AIVs) continuously cross the species barrier to infect mammalians and are repeatedly transmitted to humans, posing a significant threat to public health. Importantly, some H9N2 AIVs were found to cause lethal infection in mice, but little is known about the viral infection dynamics in vivo. To analyze the real-time infection dynamics, we described the generation of a mouse-lethal recombinant H9N2 AIV, an influenza reporter virus (VK627-NanoLuc virus) carrying a NanoLuc gene, which was available for in vivo imaging. Although attenuated for replication in MDCK cells, VK627-NanoLuc virus showed similar pathogenicity and replicative capacity in mice to its parental virus. Bioluminescent imaging of the VK627-NanoLuc virus permitted successive observations of viral infection and replication in infected mice, even following the viral clearance of a sublethal infection. Moreover, VK627-NanoLuc virus was severely restricted by the K627E mutation in PB2, as infected mice showed little weight loss and a low level of bioluminescence. In summary, we have preliminarily established a visualized tool that enables real-time observation of the infection and replication dynamics of H9N2 AIV in mice, which contributes to further understanding the mechanisms underlying the pathogenic enhancement of H9N2 AIV to mice.